Development of a Framework to Describe the Association Between Hypothetical and Real-World Decisions: A Systematic Concept Review and Cognitive Interviews with Decision Aid Developers - Hayes, Tavis (Université d'Ottawa / University of Ottawa, 2016)
Despite recommendations, health services interventions often lack mechanistic evidence. One way of acquiring such evidence is through the use of hypothetical settings. However, there are knowledge gaps about the factors that affect whether hypothetical decisions will correlate to real-world ones. This thesis involves a systematic concept review to identify the factors important to the hypothetical-real-world decision relationship and a case study of the relevance of these factors to the decision aid development context. The 42 identified factors were grouped into 5 categories: Personal Characteristics, Presentation Characteristics, Cognitive Factors, Motivation, and Participant Characteristics. Through cognitive interviews with decision aid developers we found that the interviewees had generally not considered many of the factors thought to affect the external validity of hypothetical data. This thesis contributes a framework that highlights factors for investigators to consider when designing studies in hypothetical settings and that can serve as a foundation for future research.
Keywords: Decision making; Hypothetical; Simulated; Proxy; Framework; Real; Reasoning; Health Services